Понятие и принципы формирования частной криминалистической методики - Книженко, С. А.; Knyzhenko, S. O.; Книженко, С. О.; ORCID: http://orcid.org/0000-0002-1944-4256 (Legea si viata = Закон и Жизнь: междунар. науч.-практ. журн. – 2017. – № 8/2(August). – P. 64-68, 2017)
В статье проанализированы современные научные тенденции в определении понятия частной криминалистической методики, рассмотрены разные позиции криминалистов относительно принципов формирования частных криминалистических методик. Под частной криминалистической методикой предложено понимать рекомендации типизированного характера, изложенные в описательной или формализованной форме по выявлению, расследованию и предотвращению различных преступных проявлений и судебного рассмотрения уголовных производств. Определены принципы формирования частных криминалистических методик.

The article analyzes modem scientific trends in the definition of the concept of a private criminalistic methodology, examines the different positions of criminologists regarding the principles of the formation of private forensic methods. Under a private forensic methodology, it is suggested to understand the recommendations of a typified nature, described in a descriptive or formalized form for the identification, investigation and prevention of various criminal manifestations and judicial review of criminal proceedings. The principles of the formation of private forensic methods are defined: differentiation; Adaptability; Step-by-step; Algorithmic. The principle of differentiation is aimed at accounting for criminalistic classification of crimes. The principle of adaptability is reflected in investigative (judicial) situations and the corresponding strategic and tactical tasks. Staged and algorithmic means the development of recommendations in accordance with the stages of investigation and judicial review of criminal proceedings and the identification of appropriate algorithms for the actions of the investigator and thejudge (court).

У статті проаналізовані сучасні наукові тенденції у визначенні поняття приватної криміналістичної методики, розглянуті різні позиції криміналістів щодо принципів формування приватних криміналістичних методик. Під приватною криміналістичною методикою запропоновано розуміти рекомендації типизованного характеру, викладені в описовій або формалізованої формі з виявлення, розслідування і запобігання різних злочинних проявів та судового розгляду кримінальних проваджень. Визначено принципи формування приватних криміналістичних методик.
The concept and principles of the formation of a private criminalistic methodology
Книженко, С. Понятие и принципы формирования частной криминалистической методики / Светлана Книженко // Legea si viata = Закон и Жизнь: междунар. науч.-практ. журн. – 2017. – № 8/2(August). – P. 64-68.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; расследование преступлений; криминалистическая методика; частная криминалистическая методика; розслідування злочинів; криміналістична методика; приватна криміналістична методика; investigation of crimes; forensic methodology; private forensic methodology; forensic private methods; publikatsii u zarubizhnomu vydanni